Czy prawda nas wyzwoli? Przełamywanie oporu psychologicznego w przyjmowaniu wiedzy o Zagładzie - Witkowska, Marta; Bilewicz, Michał (Zagłada Żydów. Studia i Materiały, 2014)
The introduction of the programs on Holocaust education in Poland and a broader debate on the transgressions of Poles against the Jews have not led to desired improvement in public knowledge on these historical events. A comparison of survey results from the last two decades (Bilewicz, Winiewski, Radzik, 2012) illustrates mounting ignorance: the number of Poles who acknowledge that the highest number of victims of the Nazi occupation period was Jewish systematically decreases, while the number of those who think that the highest number of victims of the wartime period was ethnically Polish, increases. Insights from the social psychological research allow to explain the psychological foundations of this resistance to acknowledge the facts about the Holocaust, and indicate the need for positive group identity as a crucial factor preventing people from recognizing such a threatening historical information. In this paper we will provide knowledge about the ways to overcome this resistance-through-denial. Implementation of such measures could allow people to accept responsibility for the misdeeds committed by their ancestors.